Wpływ koncepcji i teorii Floriana Znanieckiego na życie polskiej myśli społecznej w odniesieniu do osób starszych - Kawa, Janusz (Rocznik Pedagogiczny, 2021)
This article discusses the theoretical foundations of developed theories and their impact on the lives of older people. In this context, it is particularly important to bring closer the sociological concepts of upbringing according to Florian Znaniecki, as well as the process of transmitting norms and values. According to Znaniecki’s thesis it is the elderly, through the experience and skills acquired in the course of life, who are able to adequately convey the necessary values and norms. Possessed skills, life competences and cultural resources make that the elderly become a life guide for the younger generation, so to speak, social leaders who are able to influence their pupils. Znaniecki’s concepts and theories contributed to the development of sociology. According to the researcher, upbringing, which takes into account both the roles and the importance of the elderly and their axi- ological messages, is aimed primarily at the proper shaping of the young individual so that he/she is able to independently perform the social tasks entrusted to him/her in the future.